Phase Separation in Membrane Biology: The Interplay between Membrane-Bound Organelles and Membraneless Condensates - Zhao, Yan G.; Zhang, Hong (Developmental cell, 2020)
In eukaryotic cells, various membrane-bound organelles compartmentalize diverse cellular activities in a spatially and temporally controlled manner. Numerous membraneless organelles assembled via liquid-liquid phase separation (LLPS), known as condensates, also facilitate compartmentalization of cellular functions. Emerging evidence shows that these two organelle types interact in many biological processes. Membranes modulate the biogenesis and dynamics of phase-separated condensates by serving as assembly platforms or by forming direct contacts. Phase separation of membrane-associated proteins participates in various trafficking events, such as clustering of vesicles for temporally controlled fusion and storage, and transport of membraneless condensates on membrane-bound organelles. Phase separation also acts in cargo trafficking pathways by sorting and docking cargos for translocon-mediated transport across membranes, by shuttling cargos through the nuclear pore complex, and by triggering the formation of surrounding autophagosomes for delivery to lysosomes. The coordinated actions of membrane-bound and membraneless organelles ensure spatiotemporal control of various cellular functions. Zhao and Zhang summarize the coordinated interactions between membrane-bound organelles and membraneless condensates in various biological processes. Membranes provide surfaces for assembling condensates and also modulate their dynamics and transport, while protein phase separation regulates the storage and trafficking of membrane-bound organelles and also facilitates protein translocation across membranes.